(untitled) (Open Academia: Journal of Scholarly Research, 2026)
This article examines the theoretical, methodological, and practical foundations of strategic human resource planning in modern organizations. The research analyzes the economic, organizational, and technological dimensions of personnel planning systems and evaluates their influence on labor productivity, organizational sustainability, and competitive advantage. Particular attention is devoted to strategic, tactical, and operational planning functions, recruitment optimization, workforce placement mechanisms, HR analytics, artificial intelligence technologies, and digital decision-making systems. The study applies comparative, analytical, statistical, and systemic approaches to evaluate the effectiveness of integrated personnel planning models. Research findings demonstrate that scientifically grounded and digitally integrated human resource planning systems significantly improve labor productivity, reduce employee turnover, optimize recruitment costs, and increase overall organizational profitability. The article further explores the transformation of personnel planning under conditions of digitalization, Big Data analytics, and AI-based workforce management technologies.